2022
DOI: 10.1038/s41419-022-05005-2
|View full text |Cite
|
Sign up to set email alerts
|

Liver glycogen phosphorylase is upregulated in glioblastoma and provides a metabolic vulnerability to high dose radiation

Abstract: Channelling of glucose via glycogen, known as the glycogen shunt, may play an important role in the metabolism of brain tumours, especially in hypoxic conditions. We aimed to dissect the role of glycogen degradation in glioblastoma (GBM) response to ionising radiation (IR). Knockdown of the glycogen phosphorylase liver isoform (PYGL), but not the brain isoform (PYGB), decreased clonogenic growth and survival of GBM cell lines and sensitised them to IR doses of 10–12 Gy. Two to five days after IR exposure of PY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Furthermore, while control cells are largely resistant to DAB treatment, abrogation of glycogenolysis significantly decreases the survival of Drp1 knockdown cells. Similarly, it has been shown previously that knockdown of glycogen phosphorylase liver isoform (PYGL) sensitizes glioblastoma cells to radiation treatment [ 49 ]. It is of particular interest for future studies to determine if glycogen accumulation also provide survival advantage to cancer cells against other nutrient deprivation conditions.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, while control cells are largely resistant to DAB treatment, abrogation of glycogenolysis significantly decreases the survival of Drp1 knockdown cells. Similarly, it has been shown previously that knockdown of glycogen phosphorylase liver isoform (PYGL) sensitizes glioblastoma cells to radiation treatment [ 49 ]. It is of particular interest for future studies to determine if glycogen accumulation also provide survival advantage to cancer cells against other nutrient deprivation conditions.…”
Section: Discussionmentioning
confidence: 90%
“…The overexpression of PYGL in GBM tissues was associated with poor survival. Knockdown of PYGL decreased the growth and survival of the GBM cell line ( Zois et al, 2022 ). Our comprehensive analyses revealed that the GRMS was a hazardous biomarker for the prognosis of glioma patients, consistent with previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, the liver isoform is of interest as it catalyses the breakdown of glycogen into glucose in the liver, the inhibition of which has potential to reduce hyperglycaemia in T2DM patients [6]. Additionally, GP is also considered of promise as a target for other conditions such as myocardial and cerebral ischemias [7,8] and different cancers such as glioblastoma [9][10][11]. Seven different GP ligand-binding sites have been discovered to date: catalytic, allosteric, new allosteric, glycogen storage, inhibitor, benzimidazole and quercetin-binding sites, with the catalytic site being a focal point of research to date [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%